Observing a previously hidden structural-phase transition onset through heteroepitaxial cap response - Lan, Fanli (Proc Natl Acad Sci U S A, 2019)
Characterization of the onset of a phase transition is often challenging due to the fluctuations of the correlation length scales of the order parameters. This is especially true for second-order structural-phase transition due to minute changes involved in the relevant lattice constants. A classic example is the cubic-to-tetragonal second-order phase transition in SrTiO(3) (STO), which is so subtle that it is still unresolved. Here, we demonstrate an approach to resolve this issue by epitaxially grown rhombohedral La(0.7)Sr(0.3)MnO(3) (LSMO) thin films on the cubic STO (100) substrate. The shear strain induced nanotwinning waves in the LSMO film are extremely sensitive to the cubic-to-tetragonal structural-phase transitions of the STO substrate. Upon cooling from room temperature, the development of the nanotwinning waves is spatially inhomogeneous. Untwinned, atomically flat domains, ranging in size from 100 to 300 nm, start to appear randomly in the twinned phase between 265 and 175 K. At ∼139 K, the untwinned, atomically flat domains start to grow rapidly into micrometer scale and finally become dominant at ∼108 K. These results indicate that the low-temperature tetragonal precursor phase of STO has already nucleated at 265 K, significantly higher than the critical temperature of STO (∼105 K). Our work paves a pathway to visualize the onset stages of structural-phase transitions that are too subtle to be observed using direct-imaging methods.